Making woodblock prints - Chesterman, Merlyn; Nelson, Rod (The Crowood Press, 2015)
"Woodblock printing is an ancient art form, which produces beautiful, subtle and lively prints with just a few simple materials. This book introduces the art, and shares technical information and ideas for those with more experience. Drawing on the vibrant living traditions from China and Japan, it is both a technical guide and an inspiration."' -- Provided by publisher